PENILAIAN TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN PENDEKATAN RISIKO (Risk-Based Bank Rating) - Masnawati; Meina Wulansari Yusniar; Abdul Hadi (JWM (JURNAL WAWASAN MANAJEMEN), 2013)
This study aimed to analyze techniques of the bank’s health assessment and determine which strategies should be done in order to improve the health of the bank. The method used is the approach of Risk (Risk Based-Bank Rating) in accordance with Bank Indonesia Regulation on Rating Bank that PBI Number: 13/1/PBI/2011 which entered into force on January 1, 2012. Bank health assessment performed using four (4) factors: Risk Profile, Good Corporate Governance (GCG), Earning, and Capital. Object of this study is PT. Bank Pembangunan Daerah Kalimantan Selatan period 2012. The results showed that the health of banks in PT. Bank Pembangunan Daerah Kalimantan Selatan getting ranked 2, meaning can be categorized good. Strategies to improve the health value of a bank is to improve aspects of Earnings and Capital. Strategis Steps that must to increase credit expansion, improve the quality and quantity of human resources, product innovation, and increase fee-based income